Grading Pancreatic Neuroendocrine Tumors by Ki-67 Index Evaluated on Fine-Needle Aspiration Cell Block Material. Issue 1 (15th August 2019) - Abi-Raad, Rita; Lavik, John-Paul; Barbieri, Andrea L; Zhang, Xuchen; Adeniran, Adebowale J; Cai, Guoping
Abstract: Objectives: This study aimed to determine whether Ki-67 index evaluated on cytologic material could reliably grade pancreatic neuroendocrine tumors (PanNETs). Methods: Cases with adequate cell block and available surgical specimens were included. Ki-67 index was calculated using "eyeballing, " "hot spot, " and "complete" counting methods. Results: The overall concordance rates between cytology and surgical specimens were 71%, 73%, and 59%, respectively, by using eyeballing, hot spot, and complete counting approaches. All grade 1 tumors were correctly graded on cytology, but in grade 2 tumors concordance rates were only 36%, 41%, and 9%, respectively. All grade 2 tumors were undergraded when cell blocks contained fewer than 1, 000 cells, while concordance rate increased to 57%, 64%, and 14%, respectively, in cases with 1, 000 cells or more. Conclusions: Grade 2 PanNETs can be significantly undergraded when Ki-67 index is evaluated on cell block material. In cases with 1, 000 or more cells, the hot spot counting method has better correlation with surgical specimens.